Allevation of Oxidative Damages Induced by Salinity in Cress (Lepidium sativum) by Pretreating with Arginine - E Asadi karam; Z Asrar (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2015)
Salinity is one of the main stresses that have negative effectcs on seedling growth, and plant production. It inhibits growth of plants through disturbance of the balance between production of ROS and antioxidant defense mechanism which results in oxidative stress. Because, arginine is a vital regulator of physiological and developmental processes the effect of different concentrations of arginine pretreatment of the plant on alleviation of oxidative stress induced by salt 50 and 100Mm NaCl was investigated. Arginine pretreatment increased chlorophyll a, b, carotenoid and seedling growth under salinity condition. Results also showed that salt stress increased proline, protein, H2O2, soluble sugar and the activity of ascorbate peroxidase, guaiacol peroxidase and catalase. Pretreatment of plants with Arg reduced proline, soluble sugar, H2O2 and antioxidant enzymes activity content significantly. The conclusion is that in garden cress plants, pretreatment with concentration of 5 µM and 10 μM arginine may protect cress under salinity stress, probably through the contracting with ROS and or induction of anti-oxidative enzymes